Electrochemically activated Na-ZnCl2 battery using a carbon matrix in the cathode compartment - Lee, Younki; Kim, Han-Jun; Byun, Dong-Jin; Cho, Kwon-Koo; Ahn, Jou-Hyeon; Kim, Chang-Sam (ELSEVIER, 2019)
Sodium-metal chloride batteries have been highlighted as one of the massive energy storage systems for its intrinsically excellent safety and the use of abundant sodium. Nickel and sodium chloride have been the most studied for cathode materials because this chemistry allows high open-circuit voltage and high energy density among the candidates. However, there is a need to reduce the material cost due to costly nickel powders which are used in large quantities for the electrical connection in the cathode. This study proposes an electrochemically activated Na/ZnCl2 battery using less-expensive carbon felt to maintain efficient electron percolation in the cathode and evaluates the charge-discharge behavior and cell impedance. The Na/ZnCl2 cell, which has a capacity of 220 mAh with a new cathode configuration, significantly reduces the charge transfer resistance compared to conventional cells by approximately 42% and 62% at the 10th and 51st cycles, respectively. When the designed capacity increases to 440 mAh with the constant active area of an electrolyte, the reduction of resistance becomes apparent. This enhancement occurs because the carbon felt sufficiently conducts electrons in the cathode compartment and results in a uniform electrode reaction, which is also revealed in our analysis of the microstructure of the electrode.
Keywords: HIGH-TEMPERATURE; PERFORMANCE